Signifikansi Usaha Guru Pendidikan Agama Kristen dalam Meningkatkan Gairah Membaca Alkitab pada Siswa Kelas III di Sekolah Dasar Negeri Osiloa - Dina Dimapa; Daeng Salfina Dethan; Petrus Kefas Loka; Yublina Tefa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Christian Religious Education (PAK) is a divine and human effort carried out systematically and continuously, to transmit knowledge, values, attitudes and skills and behavior that are consistent with the Christian faith. Christian religious education is a joint political activity among pilgrims at a time that deliberately pays attention to God's activities in the present. Thus, it can be said that Christian religious education is very important in transmitting knowledge, values ​​and behavior that are consistent with the Christian faith in realizing the vision of the kingdom of God. According to Andreas, there are 2 research approaches that can be chosen, namely the positivist (quantitative) and naturalist (qualitative) approaches.